LPA Brief No. 1. Institutions, governance and incentives in common property regimes for African rangelands - Swallow, B.M.; Bromley, D.W. (International Livestock Research Institute, 1998)
About 14 % of the world's cattle and 21 % of its sheep and goats are found in Africa on a land base that comprises 25 % of the world's total area of rangelands. Most of these rangelands are or have in the past been managed under traditional systems of communal tenure. Regrettably, the wide variety of institutional arrangements, structures of governance and incentives that characterise these common property regimes have not been well understood or been the subject of much analysis. This paper attempts to fill part of this knowledge gap by providing a framework for the analysis of common property rangeland regimes on the basis of some selected examples in Africa.